Stray : a memoir - Danler, Stephanie (Alfred A. Knopf, 2020)
"From the author of the best-selling Sweetbitter comes an intimate, searingly honest memoir of growing up the child of addicts, of how that turbulent, often harrowing experience has affected her at every stage of her life, and of how she has struggled to transcend this unwanted legacy. When Sweetbitter was published to great success, the author knew she should be happy, but she felt incapable of it, emotionally shut down. She knew too that the roots of her inability to feel were deep in her childhood. With some hope of finally facing down her past--of looking clearly at her parents and what she did and did not inherit from them--she returned to California after a decade away, a decade in which she'd honed the practice of apathy. Stray is an account of that remarkable emotional journey. We meet her mother: a depressed alcoholic, now mentally and physically handicapped by a tragic brain aneurysm and living in squalor; and her father: once a successful businessman, now a constantly relapsing crystal meth addict living in halfway homes and shelters. And we are with the author as she remembers and relives the most difficult events of the ten years since she left "home"--betrayals and infidelities, her own problems with drinking, an affair with a married man whose darkness mirrored her own--and as she discovers the bounds of forgiveness, of her parents, but especially of herself."--